A new species of Pyrrhosphodrus (Hemiptera: Heteroptera: Reduviidae) from the Caatinga ecosystem in Brazil, with notes on the genus - Lapischies, Rita; Forero, Dimitri; Barcellos, Aline; Salomão, Renato P. (Zootaxa, 2019)
A new species of Reduviidae (Hemiptera: Heteroptera) from Caatinga ecosystem, Pyrrhosphodrus caatingensis Lapischies & Forero sp. nov., is described. The new species is distinguished from its congeners by its overall reddish coloration with black areas; by the black legs, with femora with a subapical yellowish broad ring, tibiae with apical and subapical yellowish annuli; and genital characters. Comments about the biology, feeding habits, habitus, genitalic images, and a distribution map of the new species are given. In addition, the following synonymy is proposed: Pyrrhosphodrus militaris Stål, 1866 = P. theresina (Berg, 1879), syn. nov. A key to separate the known species of Pyrrhosphodrus Stål, 1866 is provided.